Intergalactic Space-Time Travelers: Envisioning Globalization in Brazil’s Valley of the Dawn - Hayes, Kelly E. (Nova religio, 2013)
The Valley of the Dawn (Vale do Amanhecer) is a new Brazilian religion known for its creative synthesis of elements drawn from a diverse range of cultural and national contexts. This article considers the Valley as an example of the interrelations between religion and globalization, exploring how conceptual changes associated with contemporary processes of globalization such as time-space compression and deterritorialization function as structuring elements within the religious imaginary laid out by the Valley’s founders in the 1960s and 1970s, a period of rapid economic, social, and political change in Brazil.